SYNTHESIS OF NON-IONIC SURFACTANT FROM NEEM SEED OIL AS A POTENTIAL MATERIAL FOR ENHANCED OIL RECOVERY (EOR) - Ibrahim, A.A.; Dibis, A. A.; Muhammad, F. A.; Adefeso, I.B.; Saidu, H. M.; Makwashi, N.; Ismail, F.S. (Journal of Engineering & Technological Advances, 2025)
Surfactants are amphiphilic compounds that enable the mixing of immiscible substances like oil and water by reducing interfacial tension. However, their application in Enhanced Oil Recovery (EOR) is limited by issues such as toxicity, poor biodegradability, and dependence on edible oils, which can compromise food security. This study focused on synthesizing a non-ionic surfactant from neem (Azadirachta indica) seed oil—a non-edible, biodegradable alternative. Neem seeds were collected from Bayero University Kano, dried for six weeks, and subjected to proximate and Fourier Transform Infrared Spectroscopy (FTIR) analyses. Proximate analysis revealed 28.76% moisture, 14.44% oil/fat, 16.67% protein, and 5.1% ash. FTIR analysis identified key functional groups such as O-H, C-H, and C?N stretching. Oil extraction was carried out using Soxhlet apparatus with 800 ml of n-hexane at 65°C for 1.2 hours, yielding 23% oil, consistent with literature values. The extracted oil showed an acid value of 1.88 mg KOH/g and a saponification value of 184.8 mg KOH/g, indicating suitability for surfactant synthesis. Further FTIR analysis confirmed the presence of functional groups like C-H, C=O, CH2, CH3, C-O, and -(CH2)-n. A non-ionic surfactant was synthesized by reacting 10 ml of neem oil with 5 g NaOH at 80 °C for 2.5 hours, along with 50 ml of distilled water under continuous stirring. FTIR analysis of the product revealed characteristic O-H, COO?, and C-O functional groups, confirming successful surfactant formation. The findings support neem oil as a viable, sustainable surfactant source for EOR applications.